Adaptive COF-PVDF composite artificial solid electrolyte interphase for stable aqueous zinc batteries - Zari Tehrani (Electrochimica Acta, 2024)
The cyclability of aqueous zinc (Zn) – based batteries is limited by the formation of dendrites and side reactions. Herein, this work presents a composite- artificial solid electrolyte interphase (ASEI) in two stages. Firstly, a covalent organic framework (COF) is synthesized via an interfacial reaction between aldehyde and amine linkers. Secondly, polyvinylidene fluoride (PVDF) is additionally coated on top of the COF film via spin coating. Results demonstrate that the COF-PVDF composite regulates Zn ion flux, preventing dendrite formation and reducing side reactions, while dynamically adapting to large volume changes. Zn plating/stripping tests with a symmetrical cell reveal that PVDF@COF@Zn exhibits enhanced stability and higher coulombic efficiency (CE) compared to bare Zn. Furthermore, the full cell incorporating PVDF@COFs@Zn//I2@C signifies significantly enhanced stability, making PVDF@COFs a promising ASEI material for stable aqueous Zn batteries. It is crucial to emphasize that the chemical and mechanical properties are the key parameters in designing the ASEI, as